2022
DOI: 10.3389/fimmu.2022.1040027
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of engineered extracellular vesicles loaded quercetin nanoparticles as anti-viral therapy against SARS-CoV-2 infection: A prospective review

Abstract: Quercetin (QCT) is a naturally occurring phenolic flavonoid compound with inbuilt characteristics of antioxidant, anti-inflammatory, and immune protection. Several recent studies have shown that QCT and QCTits nanoparticles have therapeutic potential against severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection. Novel therapeutics also include the implication of extracellular vesicles (EVs) to protect from SARS-CoV-2 viral infection. This article highlighted the therapeutic/prophylactic potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 122 publications
(140 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, extracellular vesicles (EVs) are nanometer-sized lipid bilayer vesicles secreted by metabolically active cells with the potential for functional and structural modifications for organ-specific drug delivery. Compared to other delivery agents, extracellular vesicles offer several advantages, including biocompatibility; negligible systemic toxicity and adverse effects; enhanced biodistribution; and high transmission efficiency with a tendency to deliver biomolecules, including proteins, peptides, lipids, and nucleic acids [ 144 ]. Previously, extracellular vesicles showed promising potential to provide a wide range of drugs and biomolecules as carriers with significantly enhanced bioavailability and high transmission across the blood–brain barrier (BBB).…”
Section: Quercetin Particularitiesmentioning
confidence: 99%
“…On the other hand, extracellular vesicles (EVs) are nanometer-sized lipid bilayer vesicles secreted by metabolically active cells with the potential for functional and structural modifications for organ-specific drug delivery. Compared to other delivery agents, extracellular vesicles offer several advantages, including biocompatibility; negligible systemic toxicity and adverse effects; enhanced biodistribution; and high transmission efficiency with a tendency to deliver biomolecules, including proteins, peptides, lipids, and nucleic acids [ 144 ]. Previously, extracellular vesicles showed promising potential to provide a wide range of drugs and biomolecules as carriers with significantly enhanced bioavailability and high transmission across the blood–brain barrier (BBB).…”
Section: Quercetin Particularitiesmentioning
confidence: 99%
“…These methods include nasal or throat sprays (G. Williamson & Kerimi, 2020), which can achieve a high local concentration of flavanol and prevent viral entry. Other formulation strategies, include using nanosized molecules (Raghav et al, 2022), combining quercetin with metals or vitamins (Shohan et al, 2022), making enzymatic structural modifications (Shohan et al, 2022) The low bioavailability of quercetin results in a substantial portion of the bioactive compound remaining in the intestine. This can considerably affect the gut microbiota and may indirectly influence host immunity, making quercetin potentially beneficial against COVID-19.…”
Section: Highly Variable Human Pharmacokinetics Of Quercetinmentioning
confidence: 99%
“…These methods include nasal or throat sprays (G. Williamson & Kerimi, 2020), which can achieve a high local concentration of flavanol and prevent viral entry. Other formulation strategies, include using nanosized molecules (Raghav et al, 2022), combining quercetin with metals or vitamins (Shohan et al, 2022), making enzymatic structural modifications (Shohan et al, 2022), and developing more efficient phospholipid‐based delivery system (Di Pierro et al, 2021), have been suggested as means of improving the bioavailability and effectiveness of quercetin in humans. However, their effects against COVID‐19 remain unproven.…”
Section: Limited Role Of Quercetin In the Management Of Covid‐19 May ...mentioning
confidence: 99%
“…Meanwhile, modified extracellular vesicles (EVs) loaded with nanobodies against the spike protein of SARS-CoV-2 and interferon-beta, a cytokine with antiviral effects, have been reported [61][62][63][64]. EVs are biological substances with a heterogenous lipid bilayer structure that are secreted from almost all living cells and broadly classified into three types: exosomes, microvesicles, and apoptotic bodies, depending on the intracellular production mechanism [65][66][67].…”
Section: Vaccination With Nanoparticles (Lnp) and Extracellular Vesic...mentioning
confidence: 99%